2014
DOI: 10.1681/asn.2013101079
|View full text |Cite
|
Sign up to set email alerts
|

Lineage Tracing Reveals Distinctive Fates for Mesothelial Cells and Submesothelial Fibroblasts during Peritoneal Injury

Abstract: Fibrosis of the peritoneal cavity remains a serious, life-threatening problem in the treatment of kidney failure with peritoneal dialysis. The mechanism of fibrosis remains unclear partly because the fibrogenic cells have not been identified with certainty. Recent studies have proposed mesothelial cells to be an important source of myofibroblasts through the epithelial-mesenchymal transition; however, confirmatory studies in vivo are lacking. Here, we show by inducible genetic fate mapping that type I collagen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
165
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(176 citation statements)
references
References 46 publications
(76 reference statements)
5
165
1
2
Order By: Relevance
“…CreERT2 or Col1a1 GFP mice, Chen et al 25 reported that the contribution of MCs to myofibroblasts is rare in the liver. By treating Wt1…”
Section: On the Basis Of The Labeling Efficiency Of Mcs In The Wt1mentioning
confidence: 99%
See 2 more Smart Citations
“…CreERT2 or Col1a1 GFP mice, Chen et al 25 reported that the contribution of MCs to myofibroblasts is rare in the liver. By treating Wt1…”
Section: On the Basis Of The Labeling Efficiency Of Mcs In The Wt1mentioning
confidence: 99%
“…In addition, they reported that MCs are negative for GFP in the Col1a1 GFP mouse liver. Chen et al 25 did not analyze the body wall in these models. In our experimental condition, we labeled 12.5% and 14.5% of MCs in the body wall and liver, respectively, in the Wt1…”
Section: On the Basis Of The Labeling Efficiency Of Mcs In The Wt1mentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have revealed signaling pathways of angiogenesis and fibrosis in the context of epithelial mesenchymal transition (EMT) (mesothelial cell to myofibroblast) associated with PDderived peritoneal injury (for review [67,85]). However, the primary origin of myofibroblast in PD peritoneum is argued by recent insight [86]. Otherwise, the dialysate level of connective tissue growth factor (CTGF), which inhibits bone morphogenetic protein-7 (BMP-7) and activates transforming growth factor (TGF)-β (pro-fibrosis factor), was shown be correlated to high-fast PET [87].…”
Section: Pathological Findings Of Pd Associated Infectious Peritonitismentioning
confidence: 99%
“…Os miofibroblastos derivados do mesotélio seriam as responsáveis pela produção de colágeno e fibronectina resultando na fibrose peritoneal (28,36). No entanto, estudos in vivo não foram capazes de demonstrar esse fenômeno e recentemente, Chen YT e cols, demonstraram elegantemente que os miofibroblastos da camada submesotelial peritoneal se originam dos fibroblastos residentes predominantemente (37). A ativação desses fibroblastos resultaria na produção de fatores prófibróticos bem como no aumento da expressão VEGF que contribui para a neoangiogênese (38).…”
unclassified